Upaya Revitalisasi Taman Bacaan Masyarakat Humanis di SPNF SKB Wilayah I TTS - Iven Catur C. S. Tunliu; Reschi V. A. Sinlae; Samrid Neonufa (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to describe the efforts to revitalize the Humanis Community Reading Park (Taman Bacaan Masyarakat/TBM) at SPNF SKB Region I, South Central Timor Regency. The study was motivated by the condition of the Humanis TBM, which had experienced a decline in its function, poor maintenance, and limited literacy activities, resulting in its underutilization as a community learning facility. This research employed a qualitative approach using a case study method. Data were collected through observation, interviews, and documentation studies. The research informants consisted of the Head of SPNF SKB Region I, the implementer of the Humanis TBM revitalization program, and three children participating in TBM activities. Data were analyzed through data reduction, data display, and conclusion drawing, while data validity was ensured through source triangulation and technique triangulation. The findings revealed that the revitalization efforts were carried out through the stages of initial condition identification, program planning, activity implementation, and strengthening the function of the TBM. The revitalization activities included cleaning and reorganizing the reading area, classifying reading materials, utilizing digital media as a learning resource, and implementing more engaging literacy activities for children. These efforts had a positive impact on both the physical condition and function of the TBM, as indicated by improved reading space comfort, better organization of reading materials, and increased children's participation in literacy activities. Therefore, the revitalization successfully restored the function of Humanis TBM as a center for literacy and nonformal learning within the community.